Application of Interactive Technology in Library Design in Surabaya - Atika Putri K Dewi; Siti Azizah; Suci Ramadhani (Institut Teknologi Adhi Tama Surabaya, 2026)
The relatively rapid development in West Surabaya is not yet fully balanced by the availability of adequate and easily accessible educational facilities. Libraries, as centers of literacy and knowledge dissemination, are currently required to transform and keep pace with technological and societal advancements, as well as the needs of modern society. This discussion aims to explore a library design that utilizes an interactive technology approach by combining educational, recreational, and interactive functions, making it a more engaging, participatory, and relevant learning space for the current generation. The method used is descriptive qualitative thru the analysis of primary and secondary data, as well as visual documentation. The design results show the application of interactive technology on the facade and library facilities with a contemporary architecture theme, such as the use of transparent LED screens and glass walls that support natural lighting as well as informative functions. Additionally, facilities such as the Light Sensory Room, Virtual Reality, Hologram LED Board, Wall Touch Screen, and Humanoid Robotics are designed to create an immersive, innovative, and collaborative learning experience. Thus, this library not only serves as a repository of information but also as a modern educational tool that is interactive and aligned with current technological developments. Keywords : Library, Interactive Technology, and Educational